Innovation Capital - Dyer, Jeff; Furr, Nathan; Lefrandt, Curtis (Ascent Audio, 2020)
Great leaders of innovation know that creativity is not enough. They succeed not only on the basis of their ideas, but because they have the vision, reputation, and networks to win the backing needed to commercialize them. It turns out that this quality-called "innovation capital"-is measurably more important for innovation than just being creative. The authors have spent decades studying how people get great ideas (the subject of The Innovator's DNA) and how people test and develop those ideas (explored in The Innovator's Method). Now they share what they've learned from a multipronged research program designed to determine how people compete for, and obtain, resources to launch new ideas: how you can build a personal reputation for innovation; what techniques you can use to amplify your innovation capital; how you can garner attention for your ideas and projects and persuade audiences to support them; and what it means to provide visionary leadership and how you can achieve it. Featuring interviews with the superstars of innovation-individuals like Jeff Bezos (Amazon), Elon Musk (Tesla), Marc Benioff (Salesforce), Indra Nooyi (PepsiCo), and Shantanu Narayen (Adobe)-this book will help you position yourself and your ideas to compete for attention and resources so that you can launch innovations with impact.